Urban Area Design in the Arrangement of Smart Drainage Systems with IoT Technology (IoT) to Overcome Flooding in Urban Areas - Tarigan, Ruth Riah Ate; Supiyandi, Supiyandi; Lubis, Najla; Hasanuddin, Muhammad; Khodijah, Siti; Atika Rizki, Cindy (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Flooding is a major problem that frequently occurs in Medan City due to high rainfall, dense settlements, and limited drainage system capacity. Conventional drainage planning still faces obstacles in real-time monitoring of channel conditions, resulting in less than optimal flood management responses. This study aims to examine the use of Internet of Things (IoT) technology in planning a smart drainage system as a flood mitigation effort in Medan City. The research method was carried out through literature review, conceptual modeling, and analysis of IoT infrastructure needs, including water level sensors, data communication devices, and integration with geographic information systems (GIS). The results of the study indicate that the implementation of an IoT-based drainage system can improve the effectiveness of water flow monitoring, support rapid decision-making in flood control, and provide accurate spatial data for urban spatial planning. In conclusion, the use of IoT has great potential to support the development of a smart drainage system in Medan City, thereby reducing flood risk and increasing the resilience of urban infrastructure in a sustainable manner.